Implementasi Karakter Anak Dalam Terang Iman Katolik - Angela Florida Mau; Macaria Theresia Laiyan (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Children in the perspective of the Catholic faith in general are the future of the Church. Because, children are part of grace, faith, hope, and love. The social personality in question is the development of character and mentality that supports children to get to know each other. This requires self-transformation as a benchmark for understanding children's social mobility. This research was conducted at SDK Mardiwiyata 2. The method used in this research is the descriptive qualitative method. Data collection adopted research methods in the form of literature studies or reviewing articles or journals, Church documents, and books available according to the theme. Etymologically, the character comes from the Greek charessein which means to carve. From the perspective of the Catholic faith, the Church views the understanding of the concept of character education from 2 (two) points of view, namely: Faith education based on the Catechism of the Catholic Church (CCC) and faith education based on the book of canon law (KHK). The findings from this study are that children who are Catholics are dominated by non-Catholic children so through social life it appears that the character of Catholic children is less desirable, so intensive coaching is needed to shape the child's character. The conclusion this of study is the implementation of children's character in the light of the Catholic faith to improve children's character and mental development. The conclusion of this research is evident from the results of various other studies that have been done before.